Evaluation of Morphological Traits, Yield and Yield Components of Faba Bean (Vicia faba L.) under Different Levels of Chemical Fertilizers in Paddy Fields - Mohammad Rabiee; Sajjad Shaker Kouhi (پژوهش‌های حبوبات ایران, 2024)
IntroductionSustainable production is essential for ensuring food security of a growing population. Despite having a high potential for paddy fields in the northern provinces of Iran, unfortunately, most of these paddy fields are planted only once a year and farmers suffer from seasonal unemployment after rice harvesting until the next year. Second crop is one of the ways to increase land productivity and paddy farmers' income which in turn, prevents their migration. The second crop is a type of multiple cropping where the first crop is harvested before planting the second crop. Faba bean (Vicia faba L.) is an annual legume with a high protein content. Faba bean is considered an important food legume crop in Iran, especially in the northern provinces. Cultivation of faba bean as a second crop in paddy fields can help sustainable production. Efficient access to the optimum level of nutrient elements in the soil is very important for plant growth and development. The application of nitrogen, phosphorus and potassium fertilizers is one of the most appropriate methods to increase crop production. Determining the optimum levels of chemical fertilizers plays an important role in increasing the yield and sustainable production of faba bean. Therefore, the purpose of this experiment was to investigate morphological traits, yield and yield components of faba bean under different levels of nitrogen, phosphorus and potassium fertilizers in paddy fields. Materials and MethodsIn order to investigate the effects of different levels of nitrogen, phosphorus and potassium fertilizers on morphological traits, yield and yield components of faba bean in paddy fields, a factorial arrangement based on randomized complete block design with three replications was conducted in two consecutive seasons at the research fields of Rice Research Institute of Iran in Rasht. Experimental treatments were three levels of nitrogen (46, 69 and 92 kg.ha-1 from urea fertilizer source), two levels of phosphorus (48 and 96 kg.ha-1 from triple super phosphate source) and three levels of potassium (50, 75 and 100 kg.ha-1 from potassium sulfate source). A treatment without fertilizer usage was considered for an independent comparison. For measuring the yield and yield components of faba bean, ten plants in each plot were selected randomly after removing marginal effects and the traits were measured. The protein content of samples was determined by the Kejeldahl method. After measurement of the sample total nitrogen by applying factor 6.25, the seed protein content was measured. Data was analyzed using SAS 9.1 and mean comparisons were done by least significant difference (LSD) test at the 5% probability level. Results and DiscussionThe orthogonal analysis results revealed that the fertilizer treatment had a significant effect on all measured traits of faba bean. The results of variance analysis showed that nitrogen fertilizer had significant effects on all studied traits of faba bean except seeds per pod. The application of phosphorus fertilizer significantly affected branch number, pods per plant, seeds per plant, protein content, pod yield, biological yield, grain yield and protein yield. Among nitrogen levels, the highest plant height, branch number, pods per plant, seeds per plant, 100-seed weight, pod yield, biological yield, grain yield and protein yield were obtained by applying 92 kg.ha-1. The yield and yield components of faba bean were improved with increasing rate of phosphorus fertilizer, and the highest pods per plant (18.8), seeds per pod (4.6), seeds per plant (46.5), grain yield (3996.9 kg.ha-1), pod yield (13385 kg.ha-1), biological yield (34442 kg.ha-1), and protein yield (1233.2 kg.ha-1) were obtained due to addition of 96 kg.ha-1. The pods per plant, seeds per pod, pod yield, grain yield and protein yield were significantly increased with increasing rates of potassium up to 100 kg.ha-1.  ConclusionsAccording to the results and due to large areas of paddy fields in northern provinces of Iran, use of the areas for faba bean cultivation after rice harvesting can be a helpful solution for sustainable rice production, achieving self-sufficiency and ensuring food security. Overall, the results suggest that applying nitrogen (92 kg.ha-1), phosphorus (96 kg.ha-1), and potassium (100 kg.ha-1) fertilizers is recommended to achieve maximum yield and sustainable production of faba beans as a second crop in the paddy fields of Guilan province.